A Method to Improve the Performance of Arrays for Aperture-Level Simultaneous Transmit and Receive - Dujuan Hu; Xizhang Wei; Mingcong Xie; Yanqun Tang (International Journal of Antennas and Propagation)
The simultaneous transmit and receive (STAR) system needs to establish sufficiently high isolation between the transmitter and the receiver in order to play its role. However, due to the nonlinear characteristics and the accompanying noise of the active devices in the system, the coupling from the transmit channel to the receive channel cannot be accurately estimated in massive arrays, making it hard to improve the isolation between the transmit and receive channels. This paper proposes a new method to enhance isolation for aperture-level transmitting array and receiving array. The method uses the transmit and receive beamforming technology and aperture optimization technology to enhance the isolation between the transmitting aperture and the receiving aperture. The experimental results show that when the transmit power of an 8-element Vivaldi array is 30 W, the effective isotropic isolation (EII) peak value reaches 153.9 dB. The noise floor of the system is −89.9 dBm. Compared to only using aperture optimization and only using beamforming technology, the scheme in this paper, respectively, improves the isolation of 20.69 and 6.17 dB.